The Influence of Corporate Social Responsibility and Inventory Intensity on Tax Avoidance - Fitriyah Fitriyah; Liasari Fajarwati (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Although taxes play an important part in the progress of a country, businesses frequently look for ways to minimize their tax liability within the limits of the law, causing worries about various factors like corporate social responsibility and inventory levels that could be influencing this behavior. This research examines how corporate social responsibility and inventory intensity impact tax avoidance practices. The study focuses on consumer non-cyclical companies traded on the Indonesia Stock Exchange between 2018 and 2023. Using a quantitative methodology and purposive sampling, researchers selected 33 companies from an initial population of 125 firms, creating a dataset spanning six years. The analysis relied on financial statement information and employed various statistical techniques, including descriptive statistics, regression modeling, panel data estimation, classical assumption testing, and hypothesis testing. Data processing was conducted using E-Views 12 software. Key findings reveal that corporate social responsibility and inventory intensity together significantly influence tax avoidance behavior, as demonstrated by F-test results. However, analyzing individual variables using t-tests reveals that corporate social responsibility has a noticeable impact on tax avoidance, whereas inventory intensity on its own does not show a significant influence on tax avoidance behaviors.